The hygienic behaviour of Apis mellifera related to the level of infestation of Varroa destructor - Paco, A. (2021)
Hygienic behavior and the infestation level of varroa on adult bees, and the relation between those variables, were assessed on Apis mellifera bee colonies. The hygienic behavior was determined through the pin-killed test and the infestation level of varroa on adult bees was calculated on adult bee samples through the sieve technique. Correlation test between hygienic behavior and infestation level of varroa on adult bees was determined using the Spearman correlation test and SAS program 9.4 version. The hygienic behavior average value was 99,8% for the 52% highly hygienic bee colonies, while the infestation level of varroa on adult bees average value was 1,69% for the 92,3% low mite infestation colonies. Negative correlation (rs= 0,397) highly significant (p<0,01) was found. Results found suggest the existence of A. mellifera colonies with Varroa destructor resistant characteristics, due to high values of hygienic behavior and low infestation levels of varroa on adult bees> <0,01) was found. Results found suggest the existence of A. mellifera colonies with Varroa destructor resistant characteristics, due to high values of hygienic behavior and low infestation levels of varroa on adult bees.